INNOVATION OF INDONESIAN LEARNING MODELS DURING THE COVID-19 PANDEMIC: A SCIENTIFIC APPROACH WITH MULTIMEDIA (INOVASI MODEL PEMBELAJARAN BAHASA INDONESIA SAAT PANDEMI COVID-19: PENDEKATAN SAINTIFIK DENGAN MULTIMEDIA) - Syahrul Ramadhan; Atmazaki Atmazaki; Vivi Indriyani; Elfia Sukma; Ahmad Johari Sihes (Jurnal Gramatika, 2022)
The COVID-19 pandemic is the biggest problem in education worldwide. In Indonesia, a policy is put in place to implement distance learning called "School From Home". This is an e-learning assisted distance learning application. The learning model needs to be innovated so that learning can be carried out effectively. The purpose of this research is to develop an Indonesian language learning model by innovating a scientific approach with multimedia to be applied to distance learning. This model is used for high school students. This type of research is Research & Development (R&D) with a 4-D model (four D model) which consists of four stages, namely, define, design, develop, and disseminate. The product developed in this study is an Indonesian language learning model by innovating a scientific approach with multimedia. The media used to support this model include; digital teaching materials, Social Network Sited (whattsapp), Social Learning Network (Edmodo), and Zoom meetings. The product was tested in high schools (SMA N 3 Padang and SMA N 7 Padang) in January 2021. The results of this study indicate that this learning model is valid with a self-validation value of 93.35% and expert validation of 94.81. Furthermore, the learning model was tested to assess the practicality of the learning model with the value of teacher practicality of 93.13% and student validity of 83.73% in the very practical category and the value of student learning activities obtained by 91.43% in the very active category.